Thoraflex hybrid as frozen elephant trunk in chronic, residual type A and chronic type B aortic dissection. (12th December 2020) - Fiorentino, Mariafrancesca; de Beaufort, Hector W L; Sonker, Uday; Heijmen, Robin H
Abstract: OBJECTIVES: The frozen elephant trunk technique is an increasingly common treatment for extensive disease of the thoracic aorta. The objective of the study was to evaluate the outcomes of frozen elephant trunk specifically in chronic (residual) aortic dissections, focusing on downstream aortic remodelling. METHODS: Between 2013 and 2019, a total of 28 patients were treated using the Vascutek Thoraflex hybrid graft at our institution for chronic dissections/post-dissection aneurysms. Immediate and follow-up outcomes were studied, as well as the changes in total aortic diameter, true lumen and false lumen diameter and the status of the false lumen at 3 different levels of the thoraco-abdominal aorta. RESULTS: No in-hospital or 30-day mortality was observed, temporary paraparesis rate was 7% and disabling stroke incidence was 14.3%. Freedom from all-cause mortality at 2 years was 91.6 ± 5.7%, while freedom from reintervention on the downstream aorta at 2 years was 59.1 ± 10.8%. Positive aortic remodelling was achieved in 50.0%, with an enlargement in the true lumen and a reduction of the false lumen not only at the level of the proximal descending aorta with 73.1% of complete thrombosis but also at the level of the distal descending thoracic aorta, with 41.7% of complete thrombosis. CONCLUSIONS: The frozen elephant trunk is a good solution in chronic (residual) downstream aortic dissections inducing positive aortic remodelling and preventing from II stage operations or allowing an endovascular approach.